Usulan Rancangan Key Performance Indicators Menggunakan Pendekatan Perspektif Balanced Scorecard Pada PT. Pelayaran Hub Maritim Indonesia - Gayuh Mukti Rahmatullah; Amak Mohamad Yaqoub (Universitas Airlangga, 2014)
Indonesia is the largest archipelago in the world which of course, has many ports as a place reliance ship. Ports in Indonesia is always crowded by various ship activities. Such vessels require fossil fuels as the material preparation to continue the journey. This has become a business opportunity for PT. Pelayaran Hub Maritim Indonesia as a company engaged in fuel distribution. The operational activities of PT. Pelayaran Hub Maritim Indonesia has made performance measurement yet of the financial aspects only. Therefore, this study aims to design a performance measurement system for companies based on four perspectives of the balanced scorecard is a financial perspective, a marketing perspective, internal business process perspective and learning and growth perspective. This study uses a qualitative method research approach to the type of research in the form of action research case study, the data used is primary data. Data from this study obtained by interviewing the informant is determined based on the balanced scorecard perspectives. Results of this research is a performance measurement system and the weighting of each of the key performance indicators with paired comparison method to get the level of importance of each strategic objective.